Malaysia’s stormwater management and drainage master plan (pisma): a public outreach programme approach for a highland town - Mohd Sidek, Lariyah; Mohd Noor, Nur Asmaliza; Ariffin, Kamisah; Ahmad Puad, Amirah Hanim (GADING Journal for the Social Sciences, 2023)
A Public Outreach Program (POP) is used to disseminate information, solicit feedback from the various and relevant parties concerned for further improvement of a certain issue(s) and address important needs for any proposed improvements. A POP was conducted in a highland town in Malaysia with the objectives of sharing and disseminating information on on-going and future infrastructural works, as well as encouraging the general public to take responsibility in controlling erosion and sediment problems and protecting the environment. 150 participants were involved in this program involving personnels from related agencies and the public. The programme included several activities which aimed at helping authorities to find solutions to the problems of erosion and sediment in the area, and raising the public awareness on protecting the environment. The programme proposed some measures to mitigate the environmental issues, and managed to raise awareness among the target groups with regards to environmental protection.